Ocular imaging findings of bilateral optic disc pit in a child - Ozkaya, Abdullah; Alkin, Z; Taylan, AT; Demirok, A (Nepalese Journal of Ophthalmology, 2013)
Background: To report a rare condition of bilateral optic disc pit in a child. Case description: A ten-year-old female was admitted with a complaint of headache. Visual acuity was 20/20 in both eyes (OU). Anterior segment examination was normal in OU. Fundus examination revealed optic disc pit (ODP) located temporally with a diameter of 1/5 disc diameter in OU. Intraocular pressure was within normal limits in both eyes. Macular optical coherence tomography (OCT) showed a loss of retinal tissue at the site corresponding to the ODP in both eyes. Retinal nerve fiber OCT revealed decreased RNFL thickness at the temporal side of the optic nerve, corresponding to the ODP in both eyes. The patient and patient’s parents were informed about the disease and called for follow-up examinations every 6 months. In addition, the family was informed about optic pit maculopathy (OPM) and, they were told to return immediately if the patient ever complained of decreased vision in either of her eyes. After a follow-up period of 12 months, visual acuity remained stable, and no complications secondary to ODP were detected. Conclusion: Optic disc pit is diagnosed incidentally unless it is complicated with OPM. The retinal nerve fiber layer thickness is decreased at the side of the optic nerve corresponding to the ODP. Nepal J Ophthalmol 2013; 5(10): 258-261 DOI: http://dx.doi.org/10.3126/nepjoph.v5i2.8739